Revitalising historic Cairo: examining the public policy formulation and implementation - Gharib, Remah Younis (2010)
Historic Cairo is one of the major World Heritage sites due to the massive amount of built heritage and traditional societies it embraces. Since the 1980s, the historic quarters of Cairo have undergone many preservational efforts either by the local government or international organisations. Plenty of resources are being poured into the urban revitalisation process. However, with less significant outcomes except for two or three examples undertaken by non-governmental bodies. On the other hand, several policies have been generated by the government to facilitate the revitalisation of Historic Cairo with its different quarters;nevertheless, the majority continue to be ineffective and unhelpful to the local communities. The focus of this study is to examine how the government revitalizes the historic quarters,what are the policies generated during the last three decades, who are the key players in the implementation process, and what are the major challenges. This study is addressed through a qualitative, quantitative and narrative analysis with the users, officials and contributors to the process of revitalising Historic Cairo, especially Al-Gamalia and Darb Al Ahmar Quarters. The study will show the implementation of government policies in relation to the 1980 UNESCO Plan, 1997 UNDP/Supreme Council of Antiquities, and 1997 Aga Khan Trust for Culture programs for revitalising Old Cairo´s quarters. The study reveals the neglected challenges toward the communities´ rights and the revitalisation efforts focuses more on the preservation of single buildings without a comprehensive methodology of urban revitalisation and sustainable development.